Pole and Hungarian. The Two Poets – the Imagining of a State and a Poet Responsible for its Fate in the Face of Socio-Political Situation of Poland and Hungary During the Time of “Sturm und Drang” on Example of Juliusz Słowacki’s “Grób Agamemnona” and Sel - Bodzionny, Zuzanna (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
The starting point of this paper is the similarity of the socio-political situation of Poland and Hungary in the first half of the 19. century. This situation has turned out to be the leitmotif of the literature from that time. The comparison of the lyrical works of Juliusz Słowacki and Sándor Petőfi (who are thought to be the greatest poets of both nations) allows to prove in what matter the historical convergence is reflected by the analogies in portraying the attitudes of the Polish and the Hungarian living that time as well as the self-potraying of the poets who felt responsible for the fate of their countries.